AI and the creative economy : transforming content creation and influencer entrepreneurship - Boateng, Richard, 1979-; Boateng, Sheena Lovia; Anning-Dorson, Thomas; Kwame Adzaku Penu, Obed (Routledge, 2025)
In recent years, the profound impact of artificial intelligence (AI) on fostering new forms of entrepreneurship has become increasingly evident. Entrepreneurs worldwide are harnessing the capabilities of AI to develop innovative solutions and create businesses that address pressing challenges.Despite the growing recognition of AI's potential, there exists a crucial need to deepen understanding and awareness surrounding how individuals are leveraging AI to establish novel ventures. Many entrepreneurs are pioneering initiatives that deploy AI technologies to tackle complex problems. This challenge revolves around the imperative to explore, document, and comprehend the diverse ways in which AI is driving the emergence of new businesses, solving real-world problems, and reshaping the entrepreneurial landscape. It underscores the necessity for entrepreneurs, researchers, and the wider community to grasp the transformative role of AI in fostering innovation and enabling the creation of businesses dedicated to addressing societal issues. Addressing this challenge will contribute to a more comprehensive understanding of the synergy between AI and entrepreneurship, paving the way for informed and impactful ventures that leverage the full potential of AI technologies.In this respect, the purpose of this book is to offer an in-depth exploration of the intersection between AI and entrepreneurial ventures. The book aims to provide a contemporary and thorough analysis of how AI is playing a pivotal role in shaping new forms of entrepreneurship across various industries. It seeks to illuminate the ways in which entrepreneurs are leveraging AI technologies to drive innovation, address challenges, and create businesses that contribute to societal progress.Focusing on the intersection of AI and the creative economy, this book examines the role of AI in content creation, social media, and influencer entrepreneurship. It provides a snapshot of current research, identifies gaps in knowledge, and presents case studies of content creators who have successfully integrated AI into their workflows. This book highlights the impact of AI on various forms of content creation, including educational, lifestyle, health, and entertainment content. It also includes a comprehensive syllabus for training entrepreneurs on leveraging AI for content creation, emphasizing the balance between technological advancements and maintaining authenticity. --